2019
DOI: 10.1177/2055102918820640
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards depression among non-psychiatric physicians in four tertiary centres in Riyadh

Abstract: Depression is a common mental illness that has a profound impact on an estimated number of 300 million people worldwide. Depression is stigmatised in communities and even physicians, especially, non-psychiatric physicians, which affects depressed patients’ care. This study aims to investigate non-psychiatric physicians’ attitudes towards depression in Riyadh, Saudi Arabia. The study surveyed 380 participants using Revised Depression Attitude Questionnaire. Non-psychiatric physicians in Riyadh are optimistic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(66 citation statements)
references
References 18 publications
8
53
4
1
Order By: Relevance
“…Only 2 papers were set to examine self-efficacy and confidence. 21,23 Both of which were conducted in Saudi Arabia. Al-Arifi and his team recruited pharmacists, while Aldahmashi et al chose non-psychiatric physicians.…”
Section: Self-confidence and Efficacy In Helping Patients With Mental Illnessesmentioning
confidence: 99%
“…Only 2 papers were set to examine self-efficacy and confidence. 21,23 Both of which were conducted in Saudi Arabia. Al-Arifi and his team recruited pharmacists, while Aldahmashi et al chose non-psychiatric physicians.…”
Section: Self-confidence and Efficacy In Helping Patients With Mental Illnessesmentioning
confidence: 99%
“…The included studies involved 16,391 participants who were primarily adults from the community. In six studies, participants were healthcare professionals [ 12 , 19 , 24 , 26 , 27 , 37 ], and five studies were conducted among college students [ 16 , 23 , 25 , 28 , 31 , 36 ]. In general, females constituted more than half of all study participants.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported specific inclusion and exclusion criteria. Probability sampling was conducted in few studies, which renders results representative of the selected population, such as random sampling [ 38 ], cluster probability [ 26 , 27 ], and multistage stratified sampling design [ 12 , 19 , 32 34 ]. The remaining studies utilized nonprobability sampling from the community [ 13 15 , 22 – 25 , 28 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies involved 16,391 participants who were primarily adults from the community. In six studies, participants were healthcare professionals [12,19,24,26,27,37], and five studies were conducted among college students [16,23,25,28,31,36]. In general, females constituted more than half of all study participants.…”
Section: Characteristics Of the Studies And Participantsmentioning
confidence: 99%